Struktural Functionalism sebagai Proses Transmisi Kesenian Bantengan Kota Batu - Muherni Asri Utami; RR Roosita Cindrakasih (Unitri Press, 2023)
The art of the bull is an art that originated from Malang Raya, especially Batu City. The art of the bull as the name is a form of manifestation of the head of the bull animal that is used in an actual as an entertainment medium. This research examines the art of bulls from a cultural point of view using structural functionalism theory. In some structural function functionalism, namely describing the function of social structure, the process of a relationship between social reality and the general needs of social organisms so that a functioning relationship occurs. When people deal with other people in it there must be capacity as a social status and social structure called the transmission process of the arts. This study uses a qualitative approach based on the assumption of the perspective of the world of constructivism. Strategies related to this assumption are descriptive, with observation and interview methods. The interview was conducted to the bulls of the Bantengan Arts/ Art workers in Batu City, the Chairperson of the Bantengan City of Batu City, the Head of the Batu City Tourism Office and the Chairman of the Batu City Arts Council. This study can be concluded as a whole that the existence of bull art is a process of social phenomena. The existence of bull art also shows the functioning of the system and social structure through the pattern of relationships between individuals, between groups in a society. Abstrak Kesenian Bantengan adalah kesenian yang berasal dari Malang Raya Khususnya Kota Batu. Kesenian Bantengan sebagaimana namanya merupakan bentuk perwujudan kepala hewan Banteng yang digunakan secara aktraktif sebagai media hiburan. Penelitian ini mengkaji kesenian Bantengan dari sudut pandang budaya dengan menggunakan teori Structural Functionalism. Pada beberapa pemikiran structural functionalism, yaitu mendeskripsikan fungsi struktur sosial, proses satu hubungan antara kenyataan sosial dengan kebutuhan umum organisme sosial sehingga suatu hubungan berfungsi tersebut terjadi. Ketika orang berhubungan dengan orang lain didalamnya pasti ada kapasitas sebagai status sosial dan struktur sosial yang disebut dengan proses transmisi kesenian Bantengan. Penelitian ini menggunakan pendekatan kualitatif dengan didasari asumsi cara pandang dunia konstruktivisme. Strategi yang berhubungan dengan asumsi ini adalah deskriptif, dengan metode observasi dan wawancara. Wawancara dilakukan kepada pelaku Kesenian Bantengan/ pekerja seni Bantengan Kota Batu, Ketua Kesenian Bantengan Kota Batu, Kabid Budaya Dinas Pariwisata Kota Batu dan Ketua Dewan Kesenian Kota Batu. Hasil penelitian ini dapat dijelaskan bahwa keberadaan kesenian Bantengan merupakan proses fenomena sosial. Keberadaan kesenian Bantengan juga menunjukkan berfungsinya sistem dan struktur sosial melalui pola hubungan antara individu, antara kelompok didalam suatu masyarakat.